Effects of Serving as a State Functionary on Self-Rated Health: Empirical Evidence From China - He, Li; Zhang, Zixian; Wang, Jiangyin; Wang, Yuting; Li, Tianyang; Yang, Tianyi; Liu, Tianlan; Wu, Yuanyang; Zhang, Shuo; Zhang, Siqing; Yang, Hualei; Wang, Kun (Frontiers in Public Health, 2022)
Purpose: There is a strong link between occupation and self-rated health. Existing research has revealed the effects of occupation on self-rated health outcomes and the corresponding mechanisms. However, there is a lack of research on the effects of state services on self-rated health in China. Therefore, this study focuses on exploring the effects of serving as a state functionary in China on self-rated health to enrich research in related fields. Method: Based on the data of 14,138 individuals collected from the 2016 China Labour-Force Dynamics Survey, the logit model was used to investigate the effects of serving as a state functionary on self-rated health and the difference in the effects across different populations. Results: The results show that (1) serving as a state functionary has a significant positive effect on self-rated health; (2) self-rated health of elderly state functionaries is higher than that of younger state functionaries; (3) self-rated health of state functionaries in non-eastern regions is higher than that of state functionaries in eastern regions; and (4) state functionaries with lower education have higher self-rated health than highly-educated state functionaries; (5) Higher self-rated health of state functionaries is achieved primarily through better work time, better work environment and lower relative deprivation. Conclusion: Serving as a state functionary in China has a significant positive correlation with self-rated health, with differences across populations of state functionaries. This study expands the current literature on the effects of occupation on self-rated health in the context of China.